Electromagnetic wave absorbing materials, electromagnetic wave absorbing paints, electronic devices and resin parts
Patent Information
- Application Number
- JP2022534944
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-07
- Filing Date
- 2021-05-27
- Publication Date
- 2025-02-13
- Estimated Expiration
- 2041-05-27
AI Technical Summary
【0019】 本発明によれば、伸縮性および導電性の両立を図ることができる。
Smart Images

Figure 0007629460000007 
Figure 0007629460000008 
Figure 0007629460000009
Abstract
Description
[Technical field]
[0001] The present invention relates to an electromagnetic wave absorbing material, an electromagnetic wave absorbing paint, an electronic device, and a resin part. [Background technology]
[0002] The use of electromagnetic wave absorbing materials has been proposed as a means for suppressing the leakage of electromagnetic waves emitted from electronic devices and the like, as well as malfunctions of electronic devices due to external electromagnetic waves. Patent Document 1 proposes an electromagnetic wave absorbing material in which carbon nanotubes are added to silicone rubber. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2011-233834 A Summary of the Invention [Problem to be solved by the invention]
[0004] Depending on the application of the electromagnetic wave absorbing material, it is required to have considerable elasticity and to be able to be finished into various shapes. Therefore, it is preferable to maintain a mutually conductive network in the electromagnetic wave absorbing material when it is stretched or shaped into various shapes. On the other hand, although carbon nanotubes contained in the electromagnetic wave absorbing material have relatively good electrical conductivity, they generally tend to become hard. If the shape of an electronic device changes due to mechanical stress or thermal expansion, cracks may occur in the electromagnetic wave absorbing material, causing the network to break and resulting in deterioration of characteristics.
[0005] The present invention was devised under the above circumstances, and an object of the present invention is to provide an electromagnetic wave absorbing material, an electromagnetic wave absorbing paint, an electronic device, and a resin part that are capable of achieving both elasticity and electrical conductivity. [Means for solving the problem]
[0006] The electromagnetic wave absorbing material provided by a first aspect of the present invention comprises crushed carbon particles derived from carbon nanotubes.
[0007] In a preferred embodiment of the present invention, the pulverized carbon particles have a particle size of 0.5 μm to 1.5 μm as measured by dynamic light scattering, and a particle size of 15 μm to 70 μm as measured by laser scattering.
[0008] In a preferred embodiment of the present invention, the pulverized carbon particles have a particle size difference between the particle size measured by dynamic light scattering and the particle size measured by laser scattering of 15 μm or more.
[0009] In a preferred embodiment of the present invention, the adhesive is formed in a sheet shape.
[0010] In a preferred embodiment of the present invention, the sheet is made up of multiple layers stacked together.
[0011] A preferred embodiment of the present invention has layers that have a higher concentration of crushed carbon particles than other layers.
[0012] In a preferred embodiment of the present invention, the layer having a higher concentration of pulverized carbon particles than the other layers includes a layer that absorbs electromagnetic waves in a different frequency band.
[0013] In a preferred embodiment of the present invention, the magnetic layer has at least one of a layer containing a magnetic material and a layer containing a high dielectric material.
[0014] The electromagnetic wave absorbing paint provided by the second aspect of the present invention comprises crushed carbon particles derived from carbon nanotubes.
[0015] In a preferred embodiment of the present invention, the pulverized carbon particles have a particle size of 0.5 μm to 1.5 μm as measured by dynamic light scattering, and a particle size of 15 μm to 70 μm as measured by laser scattering.
[0016] In a preferred embodiment of the present invention, the pulverized carbon particles have a particle size difference between the particle size measured by dynamic light scattering and the particle size measured by laser scattering of 15 μm or more.
[0017] The electronic device provided by the third aspect of the present invention is coated with the electromagnetic wave absorbing paint provided by the second aspect of the present invention.
[0018] The resin part provided by the fourth aspect of the present invention is coated with the electromagnetic wave absorbing paint provided by the second aspect of the present invention. Effect of the Invention
[0019] According to the present invention, it is possible to achieve both stretchability and electrical conductivity.
[0020] Other features and advantages of the present invention will become more apparent from the following detailed description taken in conjunction with the accompanying drawings. [Brief description of the drawings]
[0021] [Figure 1] 1 is a cross-sectional view showing an example of an electromagnetic wave absorbing material according to the present invention. [Diagram 2] FIG. 1 is a flow diagram showing an example of a method for producing an electromagnetic wave absorbing material according to the present invention. [Diagram 3] 4 is a graph showing the measurement results of the particle size of pulverized carbon particles in an electrode layer of an example of an electromagnetic wave absorber according to the present invention. [Figure 4] 4 is a graph showing the measurement results of the particle size of pulverized carbon particles in an electrode layer of an example of an electromagnetic wave absorber according to the present invention. [Diagram 5] FIG. 4 is a cross-sectional view showing another example of an electromagnetic wave absorbing material according to the present invention. [Figure 6] FIG. 4 is a cross-sectional view showing still another example of an electromagnetic wave absorbing material according to the present invention. [Figure 7] FIG. 4 is a cross-sectional view showing still another example of an electromagnetic wave absorbing material according to the present invention. [Figure 8]FIG. 4 is a cross-sectional view showing still another example of an electromagnetic wave absorbing material according to the present invention. [Figure 9] 1 is a cross-sectional view showing an example of an electronic device in which the electromagnetic wave absorbing paint according to the present invention is used. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the drawings.
[0023] 1 shows an example of an electromagnetic wave absorbing material according to the present invention. The electromagnetic wave absorbing material A1 of this embodiment has a substrate 1 and pulverized carbon particles 2.
[0024] The use of the electromagnetic wave absorbing material A1 is not particularly limited, and it is used, for example, as a member of an electromagnetic wave shielding object for suppressing leakage or intrusion of electromagnetic waves, or as a component of an electronic device. In addition, the frequency band of the electromagnetic waves absorbed by the electromagnetic wave absorbing material A1 is not particularly limited. The electromagnetic wave absorbing material A1 of this embodiment is formed in a sheet shape.
[0025] The base material 1 is for maintaining the sheet-like shape of the electromagnetic wave absorbing material A1 and is made of an insulating material. The base material 1 is preferably made of a material that is relatively flexible and highly stretchable. Examples of materials for the base material 1 are given below.
[0026] An example of the material of the substrate 1 is an elastomer. The substrate 1 contains one or more types of elastomers (polymeric compounds having rubber-like elasticity). The type of elastomer is not particularly limited, but may be, for example, a thermosetting elastomer or a thermoplastic elastomer. A specific example of the elastomer is Quintac (registered trademark) (styrene-isoprene block copolymer) manufactured by Zeon Corporation.
[0027] The type of thermosetting elastomer is not particularly limited, but examples thereof include natural rubber, synthetic rubber, silicone rubber-based elastomers, urethane rubber-based elastomers, and fluororubber-based elastomers.
[0028] Examples of the thermoplastic elastomer include copolymers of aromatic vinyl monomers and conjugated diene monomers.Specific examples of the copolymers of aromatic vinyl monomers and conjugated diene monomers include diblock block polymers such as styrene-butadiene block copolymers and styrene-isoprene block polymers; triblock block polymers such as styrene-butadiene-styrene block polymers, styrene-isoprene-styrene block polymers (SIS), styrene-butadiene-isoprene block polymers, and styrene-isobutylene-styrene block polymers (SIBS); multiblock styrene-containing block polymers such as styrene-butadiene-styrene-butadiene block polymers, styrene-isoprene-styrene-isoprene block polymers, styrene-butadiene-styrene-isoprene block polymers, styrene-butadiene-styrene-isoprene block polymers, and styrene-isobutylene-butadiene-styrene block polymers, and hydrogenated or partially hydrogenated products thereof.Among these, block polymers such as SIS are more preferably used.
[0029] The pulverized carbon particles 2, when contained in the base material 1, impart at least localized electrical conductivity to the electromagnetic wave absorber A1, and perform the function of absorbing electromagnetic waves. The electromagnetic wave absorption by the pulverized carbon particles 2 includes, for example, the resistance component of the conductive network formed by the pulverized carbon particles 2, the RC component of the conductive network, and magnetic attenuation accompanied by heat generation. The pulverized carbon particles 2 are particles derived from carbon nanotubes obtained by pulverizing carbon tubes. Note that the electromagnetic wave absorber A1 is not limited to those containing only the pulverized carbon particles 2. In addition to the pulverized carbon particles 2, it may also contain, for example, particles made of ferrite or particles made of a high dielectric. Examples of high dielectrics include barium titanate, strontium titanate, calcium titanate, magnesium titanate, zinc titanate, lanthanum titanate, neodymium titanate, lead titanate, barium zirconate, calcium zirconate, barium stannate, calcium stannate, magnesium silicate, and the like, which can be used alone or in a mixture of two or more kinds.
[0030] 2 shows an example of a manufacturing method of the electromagnetic wave absorbing material A1. The manufacturing method of this embodiment includes a pulverized carbon particle generating step and an electromagnetic wave absorbing material generating step. The pulverized carbon particle generating step is a step of generating pulverized carbon particles 2 derived from carbon nanotubes by pulverizing carbon nanotubes. The electromagnetic wave absorbing material generating step is a step of forming the electromagnetic wave absorbing material A1 consisting of a base material 1 and pulverized carbon particles 2. The electromagnetic wave absorbing material generating step is performed, for example, by a conventionally known method such as a sheet forming process or a coating process using the pulverized carbon particles 2 obtained in the pulverized carbon particle generating step and a paste or liquid insulating material that becomes the base material 1.
[0031] <Example> An example of the pulverized carbon particle producing step will be described below. Note that the pulverized carbon particle producing step of the present invention is not limited in any way, and various methods capable of producing pulverized carbon particles that satisfy the conditions described below can be adopted.
[0032] (Pretreatment) First, single-walled carbon nanotubes (hereinafter, SWCNTs: for example, SG101 manufactured by Zeon Corporation) were mixed and dispersed in a solvent so that the content was 0.35 wt%. MEK (methyl ethyl ketone) was used as the solvent. This solution was dispersed using a high-pressure homogenizer to obtain a SWCNT dispersion (first dispersion). Next, the SWCNT dispersion liquid was left at a liquid temperature of 20 to 40° C. to remove the solvent, and then the liquid was stirred with a glass stirring rod or the like until it became powdery.
[0033] (Crushing process) The powdered SWCNT was pulverized using a planetary ball mill. A solvent was added to the pulverized SWCNT powder, and the powder was dispersed again using a high-pressure homogenizer. The solvent used was CyH (cyclohexane). The SWCNT content was 0.07 to 0.15 wt%. The redispersed SWCNT dispersion (second dispersion) was transferred to a glass container or the like, and ultrasonic vibration was applied. It was then left for 24 hours, and it was confirmed that the SWCNTs did not separate from the solvent. If separation was observed, ultrasonic vibration was applied again.
[0034] (Extraction process) After confirming that no separation of the SWCNTs from the solvent was observed, ultrasonic vibration was further applied. After leaving it for about 30 minutes, the upper part of the SWCNT dispersion near the liquid surface was sucked up with a dropper or the like and extracted into a separate container.
[0035] <Comparative Example> In Comparative Example 1, a SWCNT dispersion liquid was prepared by dispersing unpulverized SWCNTs using CyH as a solvent. In Comparative Examples 2 and 3, general carbon black was prepared. The particle size published by the carbon black manufacturer was 15 nm to 55 nm. In Comparative Example 2, a carbon black dispersion liquid was prepared using CyH as a solvent, as in the Example. In Comparative Example 3, a carbon black dispersion liquid was prepared using MEK as a solvent.
[0036] (Pre-dilution before particle size measurement) (1-1) 2 ml of each of the dispersions of Examples and Comparative Examples 1 to 3 was taken in a glass container, and IPA (isopropyl alcohol: Kanto Chemical Co., Ltd., Shika Grade 1) was added thereto to obtain a preliminary dilution solution. (1-2) The preliminary dilution in the container was stirred with a magnetic stirrer or the like, and then subjected to ultrasonic treatment under the ultrasonic conditions of frequency: 39 kHz, output: 100 W, and irradiation time: 3 minutes. (1-3) After ultrasonic treatment, the following particle size measurements were performed within 10 minutes.
[0037] <Dynamic Light Scattering> (2-1) The Zetasizer Nano series manufactured by Malvern Instruments was used as a measuring device for dynamic light scattering. The device was appropriately calibrated in advance with particle size standard particles (LTX3060A, LTX3200A) so that the measurement error was, for example, 2% or less. (2-2) 1 ml of the pre-diluted solution was placed in a 12 mm square glass cell (PCS1115) and set in the device. The glass cell was capped. (2-3) The particle information was set to a refractive index of 2.0 and an imaginary part of 0.850. (2-4) The solvent information was set as 2-Propanol, refractive index = 1.3750, and viscosity = 2.038. (2-5) The measurement temperature was set to 25°C. (2-6) The time from reaching the measurement temperature to measurement was set to 60 seconds. (2-7) The cell settings were set to “glass cuvette.” (2-8) The detector angle during measurement was set to 173°. (2-9) The time allocated for each measurement was set to “Automatic.” (2-10) The experiment was repeated three times. (2-11) “Measurement Position” was set to “Seek for measurement position” and set to automatic. (2-12) The model for smoothing the particle size distribution was set to “General Purpose.” (2-13) Z-Average was used, and the average of three measurements was taken as the measured value.
[0038] <Laser scattering method> (3-1) The measurement device used in the laser scattering method was Mastersizer 3000 manufactured by Malvern Instruments. (3-2) The particle information was set to a refractive index of 2.0 and an imaginary part of 0.850. (3-3) The solvent information was set to ethanol, refractive index = 1.3600. (3-4) The solvent used in the measurements was ethanol (Kanto Chemical, Shika Grade 1). (3-5) A specified amount of the ethanol was filled into the dispersion unit, and circulated within the device for 120 seconds.
[0039] FIG. 3 shows the results of particle size measurement by the dynamic light scattering method and the laser scattering method. As shown in FIG. 1, the particle size D1 measured by the dynamic light scattering method was distributed in the range of 0.5 μm or more and 1.5 μm or less in the Example. In the Comparative Example 1, it was distributed in the range of 1.3 μm to 5.4 μm. In the Comparative Examples 2 and 3, it was distributed in the range of 0.1 μm to 1.5 μm. On the other hand, the particle size D2 measured by the laser scattering method was 15 μm or more and 50 μm or less in the Example. In the Comparative Example 1, it was 35 μm or more. In the Comparative Examples 2 and 3, it was 15 μm or less.
[0040] FIG. 4 is a graph in which the results of particle size measurement by dynamic light scattering and laser scattering methods are summarized by the following method. The horizontal axis is the difference (D2-D1) between particle size D2 and particle size D1. The difference (D2-D1) was 15 μm or more in the Example. In Comparative Example 1, it was 32 μm or more. In Comparative Examples 2 and 3, it was distributed in the range of 0.1 μm to 15 μm. The vertical axis is the ratio (D2 / D1) between particle size D2 and particle size D1. The ratio (D2 / D1) was 15 or more in the Example. In Comparative Example 1, it was distributed in the range of 7 to 63. In Comparative Examples 2 and 3, it was distributed in the range of 0.3 to 48.
[0041] Comparing the Examples with Comparative Examples 1, 2, and 3, in FIG. 3, the Examples are the ones that satisfy the condition that the particle size D1 measured by the dynamic light scattering method is 0.5 μm or more and 1.5 μm or less, and the particle size D2 measured by the laser scattering method is 15 μm or more and 50 μm or less, and none of Comparative Examples 1 to 3 satisfy this condition (hereinafter, condition 1). Also, as can be seen from FIG. 4, only the Examples satisfy both the condition that the difference (D2-D1) between the particle size D1 measured by the dynamic light scattering method and the particle size D2 measured by the laser scattering method is 15 μm or more (hereinafter, condition 2), and the condition that the ratio (D2 / D1) between the particle size D2 measured by the laser scattering method and the particle size D1 measured by the dynamic light scattering method is 15 or more (hereinafter, condition 3), and condition 1.
[0042] <Flexibility evaluation example> An example of the results of an evaluation test of the stretchability of the electromagnetic wave absorber A1 of this embodiment will be described below.
[0043] As flexibility evaluation examples, flexibility evaluation examples 1 to 3 were prepared in which the mixing ratio of the pulverized carbon particles 2 was set to 0.5 wt%, 10 wt%, and 30 wt%. The electromagnetic wave absorbing material A1 was formed into a sheet shape of 30 mm x 15 mm and a thickness of 100 μm. As a bending test, this sheet-like electromagnetic wave absorbing material A1 was bent 360 degrees to check the occurrence of cracks, etc. As an extension test, 5 mm portions on both ends of the longitudinal direction of the electromagnetic wave absorbing material A1 were fixed with a glass epoxy resin static chuck, and the portion of the electromagnetic wave absorbing material A1 excluding the fixed portion (a portion with a length of 20 mm) was extended by 10%, and the occurrence of cracks, etc. was checked.
[0044] [Table 1]
[0045] Table 1 shows the evaluation test results of Evaluation Examples 1 to 3. As shown in Table 1, all of Flexibility Evaluation Examples 1 to 3 showed no cracks or the like in the bending test and extension test, and were found to have good flexibility.
[0046] <Example of evaluation of electromagnetic wave characteristics> The electromagnetic wave absorbing material A1 of this embodiment was subjected to an evaluation test of the electromagnetic wave absorption and shielding (electromagnetic wave characteristics), and the results are described below. The electromagnetic wave absorbing material A1 had a thickness of 400 μm.
[0047] As examples of electromagnetic wave characteristic evaluation, electromagnetic wave characteristic evaluation examples 1 to 3 were prepared in which the mixing ratio of the pulverized carbon particles 2 was set to 0.5 wt%, 10 wt%, and 30 wt%. These electromagnetic wave characteristic evaluation examples 1 to 3 were subjected to three methods, which differ for each frequency band: the KEC method (0.5 MHz to 1000 MHz), the DFFC (Dual Focus Flat Cavity) method (1 GHz to 8.5 GHz), and the FS (Free Space) method (60 GHz to 90 GHz). In the KEC method, the attenuation of the electric field (Table 2) and the magnetic field (Table 3) were measured. In the DFFC method (Table 4) and the FS method, the shielding and transmission of electromagnetic waves were measured. For the FS method, the results of the absorption characteristics (Table 5) and shielding characteristics (Table 6) are shown. In each table, the attenuation is shown in decibels.
[0048] [Table 2]
[0049] [Table 3]
[0050] [Table 4]
[0051] [Table 5]
[0052] [Table 6]
[0053] In most evaluation tests except for the FS method (absorption characteristics) in Table 5, a tendency was observed that the higher the mixing ratio, the greater the effect of absorbing and shielding electromagnetic waves. For this reason, a mixing ratio of about 30 wt% is preferable for improving the absorption and shielding effect while maintaining flexibility. On the other hand, when it is desired to improve the absorption effect by reducing the influence of reflection, as shown in Table 5, the mixing ratio can be set to 10 wt% or less, and the thickness of the electromagnetic wave absorbing material A1 can be increased or the electromagnetic wave absorbing material A1 can be laminated to increase the electromagnetic wave absorption effect.
[0054] In addition, by adding ferrite together with the pulverized carbon particles 2, the magnetic field absorption and shielding effect of the electromagnetic wave absorbing material A1 can be enhanced. The electromagnetic wave absorbing effect may be increased by stacking the electromagnetic wave absorbing material A1 to which ferrite has been added. In addition, when higher flexibility is required, the electromagnetic wave absorbing material A1 having the pulverized carbon particles 2 and another sheet containing ferrite may be stacked together. In addition, as another measure for enhancing the electromagnetic wave absorbing effect, a high dielectric such as barium titanate may be added to the electromagnetic wave absorbing material A1.
[0055] Next, the function of the electromagnetic wave absorbing material A1 will be described.
[0056] As shown in FIG. 3 and FIG. 4, the pulverized carbon particles (Example) derived from carbon nanotubes, unpulverized carbon nanotubes (Comparative Example 1) and general carbon black (Comparative Examples 2 and 3) could be clearly distinguished by condition 1. This is because the pulverized carbon particles obtained by pulverizing carbon black have different tendencies in the measurement results according to the type of particle size measurement than the unpulverized carbon nanotubes (Comparative Example 1) and carbon black (Comparative Examples 2 and 3). That is, carbon nanotubes generally tend to be in a hard state. Also, although carbon nanotubes are originally in the form of a long and thin cylinder, the cylinder is destroyed to a certain extent by pulverization and the size becomes small as a lump. However, even after pulverization, they are composed of multiple fine particles. Therefore, although the particle size D1 of the Example is unclear compared to Comparative Examples 2 and 3, the particle size D2 is clearly larger than Comparative Examples 2 and 3. Also, the particle size D1 of the Example tended to be smaller than Comparative Example 1. When this relationship was compared by the difference (D2-D1) or the ratio (D2 / D1), an even more advantageous distinction was possible.
[0057] The electromagnetic wave absorbing material A1 using the pulverized carbon particles 2 distinguished by condition 1 has good electrical conductivity derived from carbon nanotubes, while the elasticity is increased by the particle size reduction by pulverization (difference in particle size D1 from Comparative Example 2). This makes it possible to improve the elasticity of the electromagnetic wave absorbing material A1, improve the moldability into various shapes, and improve the electrical conductivity at the same time. Therefore, when the electromagnetic wave absorbing material A1 is used under various conditions, a better electromagnetic wave absorbing effect can be obtained. By distinguishing by appropriately combining condition 2 and condition 3 in addition to condition 1, it is possible to more reliably select the pulverized carbon particles 2 suitable for improving the elasticity of the electromagnetic wave absorbing material A1, improve the moldability into various shapes, and improve the electrical conductivity at the same time.
[0058] 5 shows another example of an electromagnetic wave absorbing material according to the present invention. The electromagnetic wave absorbing material A2 of this example is composed of a plurality of unit layers B. Each unit layer B has a similar structure to that of the electromagnetic wave absorbing material A1 described above. These unit layers B are stacked on top of each other and fixed to each other by bonding or the like. The concentrations of the pulverized carbon particles 2 contained in the unit layers B may be different from each other.
[0059] With such an electromagnetic wave absorbing material A2, it is possible to achieve both improved elasticity, improved moldability into various shapes, and improved electrical conductivity, similar to the electromagnetic wave absorbing material A1. Also, it is possible to more easily increase the thickness of the electromagnetic wave absorbing material A2 formed into a sheet. Furthermore, it is possible to suppress the concentration distribution of the pulverized carbon particles 2 from becoming biased in the thickness direction of the thickened electromagnetic wave absorbing material A2.
[0060] FIG. 6 shows yet another example of the electromagnetic wave absorber according to the present invention. The electromagnetic wave absorber A3 of this example is composed of a plurality of unit layers B1, B2, and B3. The unit layers B1, B2, and B3 are stacked on top of each other and fixed to each other by a method such as bonding. The unit layer B3 has a higher concentration of pulverized carbon particles 2 than the unit layers B1 and B2. The unit layer B1 includes magnetic particles 28. The magnetic particles 28 are, for example, ferrite particles. The unit layer B2 includes high dielectric particles 29. The concentration of the pulverized carbon particles 2 in the unit layers B1 and B2 is lower than the concentration of the pulverized carbon particles 2 in the unit layer B3, and may be, for example, 0. In the illustrated example, the concentration of the pulverized carbon particles 2 in the unit layers B1 and B2 is 0. The unit layer B1 absorbs electromagnetic waves in a different frequency band than the unit layer B3, and more specifically, absorbs electromagnetic waves in a lower frequency band. The unit layer B2 contributes to improving the dielectric constant, and can increase the capacitance component of the RC network that is formed. This allows the unit layer B2 to absorb electromagnetic waves in a lower frequency band. Examples of high dielectrics that form the high dielectric particles 29 include barium titanate, strontium titanate, calcium titanate, magnesium titanate, zinc titanate, lanthanum titanate, neodymium titanate, lead titanate, barium zirconate, calcium zirconate, barium stannate, calcium stannate, magnesium silicate, etc., which can be used alone or in combination of two or more.
[0061] The electromagnetic wave absorbing material A3 can achieve both improved elasticity, improved moldability into various shapes, and improved electrical conductivity, as with the electromagnetic wave absorbing materials A1 and A2. As can be seen from this example, when the electromagnetic wave absorbing material according to the present invention is formed into a sheet, its specific structure is not limited in any way. By having the unit layer B1 in addition to the unit layer B3, electromagnetic waves in a wider frequency band can be absorbed.
[0062] 7 shows yet another example of an electromagnetic wave absorbing material according to the present invention. The electromagnetic wave absorbing material A31 of this example is composed of a plurality of unit layers B1, B2, and B3, similar to the electromagnetic wave absorbing material A3 described above. The electromagnetic wave absorbing material A31 has a different structure of the unit layer B2 from that of the electromagnetic wave absorbing material A3.
[0063] The unit layer B2 of this example contains both high dielectric particles 29 and pulverized carbon particles 2. However, the concentration of pulverized carbon particles 2 in the unit layer B2 is lower than the concentration of pulverized carbon particles 2 in the unit layer B3. This type of electromagnetic wave absorber A31 can also achieve improved elasticity, improved moldability into various shapes, and improved electrical conductivity, similar to the electromagnetic wave absorbers A1 and A2. Furthermore, as can be seen from this example, when the electromagnetic wave absorber according to the present invention is formed into a sheet, its specific configuration is not limited in any way.
[0064] 8 shows yet another example of an electromagnetic wave absorbing material according to the present invention. The electromagnetic wave absorbing material A4 of this example is composed of a unit layer B. The unit layer B of this example contains magnetic particles 28 and pulverized carbon particles 2. The electromagnetic wave absorbing material 4, composed of a single unit layer B, is capable of absorbing electromagnetic waves in a wider frequency band.
[0065] 9 shows an example of an electronic device coated with the electromagnetic wave absorbing paint according to the present invention. The electronic device C of this embodiment includes an electronic element 51, a plurality of leads 52, 53a, 53b, wires 54a, 54b, a resin part 55, and an electromagnetic wave absorbing material A5.
[0066] The electronic element 51 is formed using, for example, a semiconductor, and is an element that performs various electronic functions. The leads 52, 53a, and 53b are conductive members made of, for example, a metal such as Cu. The electronic element 51 is mounted on the lead 52. One end of a wire 54a is bonded to the lead 53a, and one end of a wire 54b is bonded to the lead 53b. The wires 54a and 54b are made of, for example, a metal such as Au, and the other ends of each are bonded to the electronic element 51. The resin portion 55 covers the electronic element 51, parts of the leads 52, 53a, and 53b, and the wires 54a and 54b, and is an insulating member made of, for example, epoxy resin.
[0067] The electromagnetic wave absorbing material A5 covers the components of the electronic device C, and in the illustrated example, covers the resin part 55. The electromagnetic wave absorbing material A5 has a base material 1 and pulverized carbon particles 2, similar to the above-mentioned electromagnetic wave absorbing materials A1, A2, and A3. The electromagnetic wave absorbing material A5 is formed by coating. The electromagnetic wave absorbing material A5 is formed at a position away from the leads 53a and 53b. This is to avoid a short circuit between the leads 53a and 53b.
[0068] When the electromagnetic wave absorbing material A5 is formed by coating, it is formed by coating an electromagnetic wave absorbing paint. The electromagnetic wave absorbing paint contains a paste material or liquid material that becomes the substrate 1, and pulverized carbon particles 2 are mixed into the paste material or liquid material. An example of the paste material is silicone grease, and high viscosity silicone grease is preferable.
[0069] The electronic device C is provided with an electromagnetic wave absorbing material A5. This makes it possible to prevent electromagnetic waves from leaking from the electronic device C and electromagnetic noise from the outside from reaching the electronic element 51. Furthermore, if the electromagnetic wave absorbing material A5 is formed by coating, the electronic device C can be covered more reliably with the electromagnetic wave absorbing material A5 even if the shape of the resin part 55 of the electronic device C is complex. Furthermore, even if the shape of the electronic device C changes due to mechanical stress or thermal expansion, it is possible to prevent cracks from occurring in the electromagnetic wave absorbing material A5, thereby avoiding damage to the network and maintaining its characteristics.
[0070] Furthermore, the resin part according to the present invention includes a part body made of resin and an electromagnetic wave absorbing paint covering at least a part of the part body. As the electromagnetic wave absorbing paint, the electromagnetic wave absorbing paint in the above-mentioned embodiment may be used appropriately. The part body is not limited in any way, and examples thereof include automobile parts such as bumpers and electronic device parts such as the housings of mobile phones.
[0071] By covering at least a portion of the component body with electromagnetic wave absorbing paint, the electromagnetic noise shielding effect for the equipment, devices, etc. to which the resin component is applied is improved, and the weight can be reduced compared to a configuration in which electromagnetic noise is shielded using, for example, metal parts.
[0072] The electromagnetic wave absorbing material, the electromagnetic wave absorbing paint, the electronic device, and the resin part according to the present invention are not limited to the above-mentioned embodiment. The specific configurations of the electromagnetic wave absorbing material, the electromagnetic wave absorbing paint, and the electronic device according to the present invention can be freely designed in various ways.
Claims
1. Contains crushed carbon particles derived from carbon nanotubes, The pulverized carbon particles have a particle size of 0.5 μm or more and 1.5 μm or less as measured by a dynamic light scattering method, and a particle size of 15 μm or more and 70 μm or less as measured by a laser scattering method.
2. 2. The electromagnetic wave absorbing material according to claim 1, wherein the difference between the particle size of the pulverized carbon particles measured by the dynamic light scattering method and the particle size measured by the laser scattering method is 15 μm or more.
3. 3. The electromagnetic wave absorbing material according to claim 1, which is formed into a sheet shape.
4. 4. The electromagnetic wave absorbing material according to claim 3, which is formed in a sheet shape consisting of a plurality of layers laminated together.
5. 5. The electromagnetic radiation absorbing material of claim 4 having a layer having a higher concentration of crushed carbon particles than other layers.
6. 6. The electromagnetic wave absorber according to claim 5, wherein the layer having a higher concentration of pulverized carbon particles than the other layers has a layer that absorbs electromagnetic waves in a different frequency band.
7. 7. The electromagnetic wave absorbing material according to claim 6, comprising at least one of a layer containing a magnetic material and a layer containing a high dielectric material.
8. Contains crushed carbon particles derived from carbon nanotubes, The pulverized carbon particles have a particle size of 0.5 μm or more and 1.5 μm or less as measured by a dynamic light scattering method, and a particle size of 15 μm or more and 70 μm or less as measured by a laser scattering method.
9. 9. The electromagnetic wave absorbing paint according to claim 8, wherein the difference between the particle size of the pulverized carbon particles measured by the dynamic light scattering method and the particle size measured by the laser scattering method is 15 μm or more.
10. An electronic device coated with the electromagnetic wave absorbing paint according to claim 8 or 9.
11. A resin part coated with the electromagnetic wave absorbing paint according to claim 8 or 9.
Citation Information
Patent Citations
Thermally conductive sheet
JP2002038033A
Carbon nano-tube composite molded object and method for manufacturing the same
JP2002273741A
Electromagnetic wave absorbing material
JP2003158395A
Magnetic body
JP2009238981A
Electromagnetic wave absorber
JP2011233834A